Secondary Stresses in Trusses - Nair, R. Shankar (Engineering Journal, 1988)
Secondary stresses in steel trusses may be neglected in most cases. It is important, however, that secondary stresses be defined properly and the analysis and design be consistent with each other, as follows: If the truss members are designed for the axial forces that would occur if the members were pin-connected, then the flexural stresses indicated by a more refined analysis may be defined as secondary stresses and may be neglected, within reasonable limits. If the axial forces for member design are obtained from an analysis that includes flexural effects, flexural stresses cannot be dismissed as secondary stresses, since the presence of flexural effects in the analysis might have reduced the axial forces indicated by the analysis. In this case, the designer who wishes to neglect flexural stresses must first judge whether (and by how much) the axial forces indicated by the analysis were affected by flexural effects. And he must then make appropriate corrections in the axial forces to be used for design.